University students' awareness of breast and cervical cancers: A comparison of two countries and two different cultures - Rızalar, Selda; Avcı, İlknur Aydın; Zoladkiewicz, Paulina; Altay, Birsen; Moraczewska, Iga (AVES, 2017)
Objective: This study aims to evaluate Turkish and Polish female university students' awareness of breast and cervical cancers. The study was conducted in Turkey and Poland with 350 female students. Materials and Methods: This descriptive and cross-sectional study's data were collected using Self-Administered Form questioning students' sociodemographic characteristics and awareness of breast and cervical cancer. Data were analysed using SPSS version 16.0 for Windows with number, percentage, and chi square test. Results: According to the findings, a significant difference was found between Turkish and Polish students on knowing and applying Breast SelfExam (BSE) (p<0.05). No difference was found between the two student groups on considering mammography as required. 81.1% of Turkish and 68.1% of Polish students considered Clinical Breast Examination (CBE) as required; the difference was significant. A significantly higher number of Turkish students knew high-fat diet, overweight, first childbirth at advanced ages, and not having given birth as risk factors, while a higher number of Polish students knew using oral contraceptive as risk factor for breast cancer. A significantly higher number of Turkish students knew cancer history in family, Human Papilloma Virus, smoking, immunodeficiency, overweight, three or more full-term pregnancies, the first pregnancy at advanced ages, and poverty as risk factors for cervical cancer. A greater number of Polish students only knew using oral contraceptive as a risk factor; the difference was not statistically significant. Conclusion: Results of this study showed that breast and cervix cancer awareness is similar among university students in both countries.
WOS: 000399175900007
PubMed ID: 31244533
Keywords: Breast Cancer; Cervical Cancer; Awareness; University Students